Transformacja ustrojowa jako proces społeczny - Turska, Anna (Wydział Prawa i Administracji UAM, 1994)
The relations between transformation in the political and legal aspects and the social changes caused by that transformation have been investigated on the example of selected post-communist countries and communities. The authoress places this transformation among such concepts as solution, innovation, modernisation or revolution and discusses the changes occurring in the model of social order. On that basis a differentiation between evolutionary and anti-evolutionary approach to the problems of transformation has been made and the social acceptance of the changes analysed.
Transformation of political system as a social process